Revolution and family in rural China: influence of family background on current family wealth - Hiroshi Sato; Li Shi (Institute for the Study of Labor (IZA), 2007)
This paper examines the influence of family human capital on offspring's economic status in post reform rural China by concentrating on the father-son relationship. We focus on two indicators of family background: family class origin (jiating chengfen) and occupational experience. The results of a family wealth function for 2002 suggest that, after controlling for other individual and family characteristics, both measures of family background have a significant influence on family wealth. First, parental experience of a nonagricultural family business before collectivization has a positive and statistically significant effect on current family wealth. Second, the offspring of landlord/rich peasant and middle peasant families are more likely to have higher family wealth than poor and lower-middle peasant families. We also find cohort and regional differences in the influence of family background. Our findings suggest that the strength and robustness of the Chinese rural family as a cultural institution preserves family human capital across radical institutional changes.
Keywords: D31; 330; Family human capital; family background; intergenerational correlation; distribution of wealth; Familiensoziologie; Humankapital; Generationenbeziehungen; Lebensstandard; Vermögensverteilung; Ländlicher Raum; China